# Bounded Monotonic Sequences

If a sequence of real numbers is bounded and monotonic, then it is convergent.

## Discover Bridges #

Click on an **arrow** to get a description of the connection!

Click on an **arrow** to get a description of the connection!

__Show requirements__

__Show requirements__

Concept | Content |
---|---|

Convergence | Convergent sequences have a well-defined limit. |

Bounded Sequences | Sequences can be bounded from above and from below. The values of a bounded sequence cannot become arbitrarily large. |

Completeness | Completeness says that Cauchy sequences must converge. |

Supremum and Infimum of Sets | Bounded sets always have an supremum and infimum which are generalizations of maximum and minimum. |

__Show consequences__

__Show consequences__

Concept | Content |
---|---|

Bolzano-Weierstrass Theorem | Every bounded sequence has at least one converging subsequence. |

Leibniz Criterion | A convergence criterion for sums based on an alternating sequence. |

## Study *Bounded Monotonic Sequences* #

**Definition 1** (Monotonicity).
*A real sequence \((a_n)_{n\in\mathbb{N}}\) is called*

*monotonically increasing*if for all \(n\in\mathbb{N}\) holds \(a_n\leq a_{n+1}\).*strictly monotonically increasing*if for all \(n\in\mathbb{N}\) holds \(a_n < a_{n+1}\).*monotonically decreasing*if for all \(n\in\mathbb{N}\) holds \(a_n\geq a_{n+1}\).*strictly monotonically decreasing*if for all \(n\in\mathbb{N}\) holds \(a_n > a_{n+1}\).

We make essential use of Dedekind’s theorem to prove the following result:

**Theorem 2** (Convergence of bounded and monotonic
sequences). *Let \((a_n)_{n\in\mathbb{N}}\) be a real sequence
that has one of the following properties:*

*\((a_n)_{n\in\mathbb{N}}\) is monotonically increasing and bounded from above;**\((a_n)_{n\in\mathbb{N}}\) is monotonically decreasing and bounded from below;*

*Then \((a_n)_{n\in\mathbb{N}}\)
is convergent.*

*Proof:* Let us first assume that \((a_n)_{n\in\mathbb{N}}\) is monotonically
increasing and bounded from above. Define the set \(M=\{a_n\,:\,n\in\mathbb{N}\}\). Since \(M\) is bounded, Dedekind’s theorem implies
that there exists some \(K\in\mathbb{R}\) such that \[K=\sup M.\] We show that \(K\) is indeed the limit of the sequence
\((a_n)_{n\in\mathbb{N}}\).

Let \(\varepsilon>0\). By the
definition of the supremum, we have that \(a_n\leq K\) for all \(n\in\mathbb{N}\) and there exists some
\(N\in\mathbb{N}\) such that \(a_N>K-\varepsilon\). The monotonicity of
\((a_n)_{n\in\mathbb{N}}\) implies that
for all \(n\geq N\) holds \(a_N\leq a_n\). Altogether, we have \[K-\varepsilon<a_N\leq a_n\leq K\] and
thus \(|K-a_n|=K-a_n<\varepsilon\)
for all \(n\geq N\). This implies
convergence to \(K\).

To prove that convergence is also guaranteed in the case where \((a_n)_{n\in\mathbb{N}}\) is monotonically
decreasing and bounded from below, we consider the sequence \((-a_n)_{n\in\mathbb{N}}\), which is now
bounded from above and monotonically increasing. By the (already proven)
first statement of this theorem, the sequence \((-a_n)_{n\in\mathbb{N}}\) is convergent,
whence \((a_n)_{n\in\mathbb{N}}\) is
convergent as well.\(\Box\)

**Remark 3**. By the same argumentation as in Remark
from page , the monotone increase (decrease) of \((a_n)_{n\in\mathbb{N}}\) can be slightly
relaxed by only claiming that \(a_n\leq
a_{n+1}\) (\(a_n\geq a_{n+1}\))
for all \(n\geq n_0\) for some \(n_0\) in \(\mathbb{N}\). In such a case, the limit of
the sequence is then given by \(\sup\{a_n\,:\,n\geq n_0\}\) (resp. \(\inf\{a_n\,:\,n\geq n_0\}\)).

**Example 4**.

Consider the sequence \((a_n)_{n\in\mathbb{N}}\) which is recursively defined via \(a_1=1\) and \[a_{n+1}=\frac{a_n+\frac2{a_n}}{2}\;\text{ for $n\geq 1$.}\] We now prove that this sequence is convergent by showing that it is bounded from below and for all \(n\geq2\) holds \(a_{n+1}\leq a_n\).

*Proof:*To show boundedness from below, we use the inequality \(\sqrt{xy}\leq\frac{x+y}2\) for all nonnegative \(x,y\in\mathbb{R}\). This inequality is a consequence of \[0\leq\frac{(\sqrt{x}-\sqrt{y})^2}2=\frac{x+y}2-\sqrt{xy}.\] The first inequality is a consequence of the fact that squares of real numbers cannot be negative.

Using this inequality, we obtain for \(n\geq1\) \[a_{n+1}=\frac{a_n+\frac{2}{a_n}}{2}\geq \sqrt{a_n\cdot\frac2{a_n}}=\sqrt{2}.\] Thus, \((a_n)\) is bounded from below. For showing monotonicity, we consider \[a_{n+1}-a_n=\frac{a_n+\frac2{a_n}}{2}-a_n=\frac{1}{2a_n}(2-a_n^2).\] In particular, if \(n\geq2\), we have that \(a_n>0\) and \(2-a_n^2\leq0\). Thus, \(a_{n+1}-a_n\leq0\) for \(n\geq2\). An application of Theorem 2 (resp. the slight generalisation in Remark from above) now leads to the existence of some \(a\in\mathbb{R}\) with \(a=\lim_{n \to\infty}a_n\).

To compute the limit, we make use of the relation \(\lim_{n \to\infty}a_n=\lim_{n\to\infty}a_{n+1}\) (follows directly from the Definition of limits) and the formulae for limits. This yields \[a=\lim_{n \to\infty}a_n=\lim_{n\to\infty}a_{n+1}=\lim_{n\to\infty}\frac{a_n+\frac2{a_n}}{2}=\frac{a+\frac2{a}}{2}.\] This relation leads to the equation \(2-a^2=0\), i.e., we either have \(a=\sqrt{2}\) or \(a=-\sqrt{2}\). However, the latter solution cannot be a limit since all sequence elements are positive. Therefore, we have \[\lim_{n\to\infty}a_n=\sqrt{2}.\]Let \(x\in\mathbb{R}\) with \(x>1\). Consider the sequence \((\sqrt[n]{x})_{n\in\mathbb{N}}\). It can be directly seen that \((\sqrt[n]{x})_{n\in\mathbb{N}}\) is monotonically decreasing and bounded from below by one. Therefore, the limit \[a=\lim_{n\to\infty}\sqrt[n]{x}\] exists with \(a\geq1\). To show that \(a=1\), we assume that \(a>1\) and lead this to a contradiction.

The equation \(a>1\) leads to the existence of some \(n\in\mathbb{N}\) with \(a^n>x\), and thus \(a>\sqrt[n]{x}\). On the other hand, the monotone decrease of \((\sqrt[n]{x})_{n\in\mathbb{N}}\) implies that \[a=\lim_{n \to \infty}\sqrt[n]{x}=\inf\{\sqrt[n]{x}\,:\,n\in\mathbb{N}\}<a,\] which is a contradiction.Let \(x\in\mathbb{R}\) with \(0< x<1\). Consider the sequence \((a_n)_{n\in\mathbb{N}}=(\sqrt[n]{x})_{n\in\mathbb{N}}\). Then we have by Example b) and the rules for calculating limits that \[\lim_{n\to\infty}\sqrt[n]{x}=\frac1{\lim_{n\to\infty}\sqrt[n]{\frac1x}}=\frac11=1.\]

Let \((a_{n})\) be a nonnegative sequence with \(a_{n}\rightarrow a\) and \(k\in\mathbb{N}\). Then for all \(\varepsilon>0\) there exists \(N>0\) such that \(|a_{n}-a|<\varepsilon^{k}\). From this it follows that \[|\sqrt[k]{a_{n}}-\sqrt[k]{a}|\leq \sqrt[k]{|a_{n}-a|}<\varepsilon.\] Thus \((\sqrt[k]{a_{n}})\) is convergent with limit \(\sqrt[k]{a}\).

The sequence \((a_{n})_{n\in\mathbb{N}}\) defined as \(a_{n} := \left(1+\frac{1}{n}\right)^{n}\) is convergent.

**Remark 5**. The limit of the sequence \[(a_n)_{n \in \mathbb{N}N} =
\left( \Big(1+\frac{1}{n} \,\Big)^{n}\right)_{n \in
\mathbb{N}},\] i.e. \(e:=\lim_{n\rightarrow\infty}\left(1+\frac{1}{n}\right)^{n}\)
is well known as *Euler’s number*. Later on we will define the
exponential function \(\exp\). It holds
that \(e=\exp(1)\approx 2.7182818...\)
. Indeed, we will show later on that \(e^{z}=\lim_{n\rightarrow\infty}\left(1+\frac{z}{n}\right)^{n}=\exp(z)\).

#### Discuss your questions by typing below.

## Solve the WeBWorK Exercise #

_{The data for the interactive network on this webpage was generated with pntfx Copyright Fabian Gabel and Julian Großmann. pntfx is licensed under the MIT license. Visualization of the network uses the open-source graph theory library Cytoscape.js licensed under the MIT license.
}